Specific Sequence Motif of Var Gene as Predictor of Malaria Outcome - Erma Sulistyaningsih; Rosita Dewi; Sheilla Rachmania; Irawan Fajar Kusuma; Sahrir Sillehu (Elkawnie, 2024)
Abstract: The Var gene family encodes for Plasmodium falciparum Erythrocyte Membrane Protein-1 (PfEMP1), a protein responsible for malaria pathogenesis. One of the variants, the var D gene, is hypothesized as a predictor of clinical malaria outcomes. The study aimed to investigate the association between the expression of the var D gene and clinical malaria outcomes. Blood spots on filter paper from uncomplicated and severe malaria patients were collected for DNA and RNA extraction. The RNA was reverse-transcribed into cDNA. DNA and cDNA were amplified by Polymerase Chain Reaction (PCR) technique using specific var D primer, and PCR products were electrophorized in 1% agarose. DNA amplification resulted in double bands of approximately 230 bp and 250 bp in uncomplicated and severe malaria samples. However, the cDNA amplification generated a single band of 230 bp from four out of five severe malaria samples. The existence of band solely in severe malaria transcript suggested its involvement in the pathogenesis of severe malaria. In conclusion, the expression of var D gene-specific sequence can be a potential predictor of severe malaria outcomes.Abstrak: Famili gen var mengkode Plasmodium falciparum Erythrocyte Membrane Protein-1 (PfEMP1), suatu protein yang berperan penting dalam proses patogenesis malaria. Salah satu variannya, gen var D, diduga merupakan prediktor gambaran klinis malaria. Penelitian ini bertujuan untuk mengetahui hubungan antara ekspresi gen var D  dan gambaran klinis malaria. Sampel berupa tetesan darah pada kertas filter dari pasien malaria tanpa komplikasi dan malaria berat dikumpulkan untuk diekstraksi DNA dan RNAnya. RNA selanjutnya di trankripsi reverse menjadi cDNA. DNA dan cDNA diamplifikasi dengan teknik PCR menggunakan primer spesifik var D dan produk PCR dielektroforesis menggunakan agarosa 1 %. Amplifikasi DNA menghasilkan beragam pita berukuran sekitar 230 bp dan 250 bp pada sampel malaria tanpa komplikasi dan malaria berat, tetapi amplifikasi cDNA hanya menunjukkan satu pita berukuran 230 bp pada 4 dari 5 sampel malaria berat. Keberadaan pita hanya pada sampel malaria berat mengindikasikan peran gen ini dalam patogenesis malaria berat. Disimpulkan bahwa gen var D dapat ditemukan pada sampel malaria tanpa komplikasi dan berat, namun ekpresi gen tersebut dapat menjadi prediktor yang potensial  timbulnya manifestasi klinis malaria berat.